2001
DOI: 10.1046/j.1440-1827.2001.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell differentiation and apoptosis of monocytic and promyelocytic leukemia cells (U‐937 and HL‐60) by tryptanthrin, an active ingredient of Polygonum tinctorium Lour.

Abstract: Tryptanthrin, a bioactive ingredient of Polygonum tinctorium Lour., is a member of the Indigo plant family and has potent cytocidal effects on various human leukemia cells in vitro. At low concentrations, tryptanthrin enhanced the expression of cell differentiation (CD) markers in human monocytic (U-937) and promyelocytic (HL-60) leukemia cells indicative of differentiation to monocytes/macrophages. Furthermore, nitroblue tetrazolium (NBT) reductive and alpha-naphthyl butyrate esterase (NBE) activities were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 23 publications
1
59
1
Order By: Relevance
“…Tryptanthrin with chemical name indolo [2,1-b] quinazolin-6,12-dione was reported to carry anti-microbial activity against a variety of microorganisms including bacteria, yeasts, dermatophytes and phytopathogens [10,11] . Recently, tryptanthrin has been paid much attention as an aryl hydrocarbon receptor agonist [12] , anti-inflammatory agent [13] , inducer of caspase-3/Fas mediated apoptosis [14] , cytostatic agent [15] and drug resistance reversal agent [16] . In this study, a series of tryptanthrin derivatives were synthesized and designated as compounds 1-7.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptanthrin with chemical name indolo [2,1-b] quinazolin-6,12-dione was reported to carry anti-microbial activity against a variety of microorganisms including bacteria, yeasts, dermatophytes and phytopathogens [10,11] . Recently, tryptanthrin has been paid much attention as an aryl hydrocarbon receptor agonist [12] , anti-inflammatory agent [13] , inducer of caspase-3/Fas mediated apoptosis [14] , cytostatic agent [15] and drug resistance reversal agent [16] . In this study, a series of tryptanthrin derivatives were synthesized and designated as compounds 1-7.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptanthrin is a phytochemical found in the medicinal indigo plants such as Polygonum tinctorium and Isatis tinctoria. It was found to possess a wide spectrum of biological and pharmacological activities, including anti-microbial (7-9), immunomodulatory (11-13), antiinflammatory (13-15) and anti-tumor (16)(17)(18)(19) activities. A previous report has shown that tryptanthrin is able to induce both apoptosis and differentiation in the human leukemia HL-60 cells and U-937 cells in vitro (16), however, the underlying action mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to possess a wide spectrum of biological and pharmacological activities, including anti-microbial (7-9), immunomodulatory (11-13), antiinflammatory (13-15) and anti-tumor (16)(17)(18)(19) activities. A previous report has shown that tryptanthrin is able to induce both apoptosis and differentiation in the human leukemia HL-60 cells and U-937 cells in vitro (16), however, the underlying action mechanisms remain unclear. In this study, the anti-proliferative and differentiation-inducing activities of tryptanthrin on the murine myelomonocytic leukemia WEHI-3B JCS cells were investigated and the possible anti-tumor mechanisms were elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations